Human Right to Water and Sanitation: Water for All vs. Full Cost Recovery - Sereno, Amparo (Frontiers in Water, 2022)
The present work starts from the definition of the concept “human right to water and sanitation” (HRWS). Then, it delimits its content, in a strict sense, to finally argue that it is an autonomous and subjective right. In other words, it is a right of immediate applicability, which means that it binds both the State and the private sector – that is, public or private supply and sanitation companies. Therefore, there is a minimum that cannot be denied to anyone, especially to individuals or families who cannot afford to pay their water bills. Next, I propose possible solutions for water and sanitation companies to ensure HRWS – avoiding water cuff-off – without compromising their economic and financial sustainability. Finally, I conclude that to comply with the principle of full cost recovery (FCR) – established by the EU Water Framework Directive (FWD) – the water bill will have to progressively increase – especially in regions where water is scarce and (due to the effects of climate change) will become an increasingly precious good. But, for those who cannot afford to pay the water bill, State will have to subsidize to guarantee the minimum service, per person and per day, which is a human right.